2014
DOI: 10.3109/09638237.2014.880408
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination against people with a mental health diagnosis: qualitative analysis of reported experiences

Abstract: Discrimination should be understood as occurring within social relationships and influenced by expectations of contact within these relationships. A better understanding of these processes can help target more effective messages in anti-discrimination campaigns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
28
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 19 publications
5
28
0
Order By: Relevance
“…Emotional closeness was important for recovery; much of this resource is provided by family or friends Stigma Families are impacted by public attitudes to mental illness: we found evidence of courtesy stigma 230 in networks. We also found families generate stigma 231 and their lack of understanding can amplify the difficulties people with SMI experience. We also learnt that people often developed effective coping strategies for dealing with 'challenging' family relationships, sometimes aided by practitioners…”
Section: Social Supportmentioning
confidence: 79%
“…Emotional closeness was important for recovery; much of this resource is provided by family or friends Stigma Families are impacted by public attitudes to mental illness: we found evidence of courtesy stigma 230 in networks. We also found families generate stigma 231 and their lack of understanding can amplify the difficulties people with SMI experience. We also learnt that people often developed effective coping strategies for dealing with 'challenging' family relationships, sometimes aided by practitioners…”
Section: Social Supportmentioning
confidence: 79%
“…These measures were chosen since a previous study found that the common factors effective in a therapeutic relationship (i.e., positive regard, empathy, unconditionality) differentiated peer providers from regular providers at the initial stage of the therapeutic relationship [2]. Given that the general public is known to harbor negative stereotypes of persons with mental illnesses [17][18][19][20][21] and might therefore be afraid to receive care from a person with mental illness while typically having faith in physicians, we predicted that those thought to be psychiatrists would be rated as more likeable, effective, and desirable for returning for care.…”
Section: Introductionmentioning
confidence: 99%
“…Mental health difficulties affect approximately one third of children, covering emotional, neurodevelopmental and behavioural disorders (Merikangas et al, 2009) and many adults and children diagnosed experience discrimination and stigma (Hamilton et al, 2014). Differentiating developmental norms from mental health difficulties requires mental health services to provide an initial assessment.…”
Section: Introductionmentioning
confidence: 99%